A study on the validity of the current final English test for the 2nd semester non-English majors at Hanoi University of Industry = Nghiên cứu về tính xác thực của bài thi tiếng Anh cuối học kỳ thứ hai hiện nay dành cho sinh viên không chuyên tiếng Anh tạ - Nguyen, Van Bac (University of Languages and International Studies, 2017)
Chapter 1-Introduction-provides background to the study, identifies the problems, states the aim, purpose and significance of the study, the scope, the methods, the research questions and the design of the study. Chapter 2 -Literature review-Presents a review of related literature that provides the theoretical background of the testing and evaluation in generaland the test validity in 4particular. This review also provides an overview of other studies related to testing, evaluation, especially the evaluation of tests in terms of its validity. Chapter 3 -The Study-Provides information about the subjects of thestudy. It then describes the data collection instruments and data collection procedure. The rationale for choosing such data collection instruments is also provided.Chapter 4 -Findings and Discussions-Analyses and discusses the data collected to reveal the real results and the validity of the final 2ndsemester exam for non English major students of HaUI. The causes for any problems if any and some implications for effective final achievement tests will be also discovered.Chapter 5 -Conclusion-Summarizes the major findings that are hoped to find the appropriate way to enhance the validity of final achievement tests to non English majors. Limitation of the study and suggestions for further research are also given in this chapter.